Relative palatability and efficacy of brodifacoum-25D conservation rodenticide pellets for mouse eradication on Midway Atoll - Peter J. Kappes; Shane R. Siers; Israel L. Leinbach; Robert T. Sugihara; Wesley J. Jolley; Jonathan H. Plissner; Elizabeth N. Flint; Kelly L. Goodale; Gregg R. Howald (Biological Invasions, 2022)
Invasive mice ( Mus spp.) can negatively impact island species and ecosystems. Because fewer island rodent eradications have been attempted for mice compared to rats ( Rattus spp.), less is known about efficacy and palatability of rodenticide baits for mouse eradications. We performed a series of bait acceptance and efficacy cage trials using a standard formulation of brodifacoum-based rodenticide on wild-caught mice from Sand Island, Midway Atoll, to help inform a proposed eradication there. Mice were offered ad libitum brodifacoum pellets along with various alternative food sources, and a “no choice” treatment group received only bait pellets. Mortality in the no choice trial was 100%; however, when offered alternative foods, mice preferred the alternative diets to the bait, leading to low mortality (40%). Because there was concern that the bittering agent Bitrex® in the formulation may have reduced palatability, we conducted a subsequent trial comparing brodifacoum bait with and without Bitrex. Mortality in the with-Bitrex treatment group was slightly higher, indicating that the bittering agent was not likely responsible for low efficacy. Laboratory trials cannot account for the numerous environmental and behavioral factors that influence bait acceptance nor replicate the true availability of alternative food sources in the environment, so low efficacy results from these trials should be interpreted cautiously and not necessarily as a measure of the likelihood of success or failure of a proposed eradication.